2021
DOI: 10.3390/electronics10161957
|View full text |Cite
|
Sign up to set email alerts
|

A Configurable RO-PUF for Securing Embedded Systems Implemented on Programmable Devices

Abstract: Improving the security of electronic devices that support innovative critical services (digital administrative services, e-health, e-shopping, and on-line banking) is essential to lay the foundations of a secure digital society. Security schemes based on Physical Unclonable Functions (PUFs) take advantage of intrinsic characteristics of the hardware for the online generation of unique digital identifiers and cryptographic keys that allow to ensure the protection of the devices against counterfeiting and to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…On the other hand, multiple competitions of the same pair of ROs will also produce slightly different results, as a consequence of changes in operating conditions and the possible presence of different sources of noise in the device that implements the system. The results obtained in the characterization of the RO-PUF presented in [10] experimentally demonstrated that stability and entropy are inversely proportional when analyzing these properties for each of the bits of the counters. The characterization process showed that the four LSBs correspond to the most unstable bits and therefore represent the highest level of entropy within each number generated by the losing counters.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, multiple competitions of the same pair of ROs will also produce slightly different results, as a consequence of changes in operating conditions and the possible presence of different sources of noise in the device that implements the system. The results obtained in the characterization of the RO-PUF presented in [10] experimentally demonstrated that stability and entropy are inversely proportional when analyzing these properties for each of the bits of the counters. The characterization process showed that the four LSBs correspond to the most unstable bits and therefore represent the highest level of entropy within each number generated by the losing counters.…”
Section: Introductionmentioning
confidence: 94%
“…This paper presents a TRNG, developed from an existing RO-PUF circuit [10], designed in VHDL language for the Xilinx Zynq-7000 family devices and implemented on the Pynq-Z2 development board. This design also uses the strategy of comparing RO pairs to generate random bits, but differs from the last referenced work in the way the RO pairs are selected to perform such counts, allowing us to explore different competition strategies [11], which in our context represents different options to build a TRNG.…”
Section: Introductionmentioning
confidence: 99%
“…The output of the RO-PUF is a bitstream conformed by the concatenation of the bits selected for each of the comparisons after the complete challenges sequence has been applied. However, in our contribution, two simultaneous comparisons will be carried out in parallel taking advantage of the two different behaviors identified in [19], depending on whether the comparison is made between two ROs implemented in LookUp Tables (LUTs) placed in the same position of different CLBs or between ROs implemented in LUTs placed in different positions within the same or a different CLB, thus doubling the bit generation rate in the PUF response. The selection and enabling signals for the two pairs of ROs to be compared in each comparison cycle are provided, respectively, by the challenge generation (ro_chl) and enable (ro_en) blocks.…”
Section: Ro-puf Ip Module Design and Implementationmentioning
confidence: 99%
“…The operating principle of silicon PUFs is based on the variations that arise during the manufacturing process of an integrated circuit. Roughly, research on silicon PUFs has focused on three categories: (i) memory-based PUFs (SRAM [7], DRAM [8,9]) that use unpredictable start-up values of memory cells; (ii) delay-based PUFs that use the relative time delay differences between two theoretically identical circuits (Ring oscillators [10]- [19], Arbiter [20], Butterfly [21]); and (iii) analog PUFs that exploit measurements of variables in mixed-signal and analog integrated circuits (for instance, current mirrors [22]).…”
Section: Introductionmentioning
confidence: 99%
“…Two groups of silicon PUFs are usually distinguished in the literature based on the circuitry utilized to exploit intrinsic variability in the Integrated Circuit (IC) manufacturing process: memory-based and delay-based PUFs. Memory-based PUFs (SRAM [14], DRAM [15,16]), rely on the erratic start-up values of memory cells when the circuit is turned on, while delay-based PUFs (Ring oscillators (ROs) [17][18][19][20][21][22][23][24][25][26], Arbiter [27], Butterfly [28]), take advantage of the differences in delays in signal transmission through two ideally identical paths of an electronic circuit. The on-chip memories of programmable devices are typically initialized to a fixed value after startup, making SRAM-based PUFs impractical for these devices.…”
Section: Introductionmentioning
confidence: 99%